Rare Karma-pa texts on the practice of the Mahamudra ; the six doctrines of Naropa ; and other esoteric precepts (Kandro, 1974)
Teachings of the Karma Kargyudpa tradition of Tibetan Lamaism on esoteric yogic and ritual practice.